CUSTOMER BENCHMARKING ANALYSIS ON BRAND IMAGE FORMATION IN BRAND NIKE - Ayungga, Rhegie Nastiti (Economic and Bussiness Faculty, Dr Soetomo University, 2018)
This study aims to analyze customer benchmarking through the effect of brand identity to the formation of brand image on the Nike brand through brand awareness. Samples were selected from respondents from athletes athletics, aquatic, football, basketball, and coaches in each branch, as well as those who have an awareness exercise encountered by researchers in the area of GOR Surabaya Koni and sports clubs in East Java. Data collection techniques using primary data by distributing questionnaires to the respondents. Data were analyzed using SPSS version 23.0 with path analysis. The results of this study indicate that the brand identity and brand awareness proven effect on simultaneously on the brand image of the Brand Nike. When viewed from the direct influence, brand identity diclared effect on brand awareness, and brand awareness is evident influence on brand image. Meanwhile, if viewed from the indirect effect, stated that the brand identity can not affect the brand image through brand awareness. Limitations in this research is the study population used is limited to several sports clubs in East Java is the target population.